Development of Kvisoft Flipbook Maker Media on Integrated Thematic Learning in Fifth Grade of Elementary School - Reinita, Reinita; Saralee, Adelweiss (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
This research is motivated by the unavailability of varied and monotonous learning media. This results in a conventional learning situation where learning is only centered on the teacher and students only get information. and also caused by the lack of creativity of teachers in building interesting learning media. This study aims to develop a Kvisoft Flipbook Maker media based on a scientific approach in integrated thematic learning in grade V Elementary School that is valid and practical. This type of research is development using the ADDIE model. The product developed is the Kvisoft Flipbook Maker media based on a scientific approach in Theme 8 (Our Friendly Environment) sub-theme 1 (Humans and the Environment) Learning 3 and 4. The results of the practicality test can be seen in the questionnaire responses of students and teachers. Where the overall student response questionnaire as many as 10 people is 97% in the very practical category and the teacher's questionnaire response is 95.7% in the very practical category. Thus, the Kvisoft Flipbook Maker media based on a scientific approach is declared practical to be used in learning activities.